The politics of irrigation reform in Tajikistan - Sehring, Jenniver; Justus Liebig University Giessen (My University, 2006)
The present study was compiled within the framework of the research project "Water Shortage, Water Use Conflicts and Water Management in Arid Environments of Central Asia". Its objective is to analyze the causes and the effects of the growing water shortage and the increasing deterioration of the water quality in this region. The research activities compare the situation in four inland basins of Central Asia: the Aral Sea Basin, the Ili-Balkhash Basin, the Issyk-Kul Basin, and the Tarim Basin. One component of the project focuses on questions of water management on interstate as well as national level.
Keywords: ddc:630